Anti-inflammatory potential of Curcumin in the treatment of Ulcerative Colitis: a review article - Teixeira, Maria Luiza Machado; Ruviaro, Vanessa; Vizzotto, Bruno Stefanello; Rech, Virginia Cielo (Disciplinarum Scientia | Naturais e Tecnológicas, 2023)
Curcumin is frequently used to treat inflammatory conditions such as ulcerative colitis (UC), characterized by irritation and ulceration within the intestinal colon. Nevertheless, its limited solubility in aqueous solutions and challenges in terms of bioavailability often impact the efficacy of treatments. UC is known to have multifactorial pathogenesis, with genetic, infectious, immunological, and dietary factors contributing to its occurrence. Its manifestations include bloody diarrhea, cramps, and abdominal tenderness. The objective of this study was to conduct an exploratory and qualitative literature review concerning the utilization of curcumin for managing UC. Upon analyzing the gathered literature, it becomes evident that curcumin exhibits exceptional anti-inflammatory properties. Notably, the most favorable outcomes are observed when employing nanostructured curcumin, which enhances permeability, bioavailability, and aqueous solubility. In cases of UC, the pronounced inflammatory processes can even result in the development of neoplasms. In the reviewed studies on colitis, curcumin proves to be a therapeutic option by reducing the inflammatory process. Moreover, when combined with medications used for colitis treatment, curcumin enhances the effects of these drugs, making them more effective than when used alone to treat this disease.